Meningkatkan Disiplin dan Tanggung Jawab Siswa Melalui sanksi Berjenjang pada Siswa Kelas III SD - Aripin Aripin (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2019)
The main objective of this study was to determine the level of discipline and sense of responsibility of third grade students. The step of this research is from planning, observation before implementation, research, observation during the implementation of the research from cycle I to cycle II and data processing is done in a descriptive comparative manner and reflections from each cycle are held. Obtained results in the first cycle that the category of student discipline level value is still low, namely sufficient value C. While in the category of sense of responsibility students achieve sufficient value C, which is the average value of 6.7. But at the point of doing homework with a value D that is 5.4. In the second cycle the results were the level of discipline students, reaching an average score of 8.6 (very good category). The level of responsibility of students reaches a value of 8.5 (very good). In the category of doing homework, which is only able to reach the value in sufficient category C, which is an average value of 6.7. It was concluded that there was an increase in the level of discipline and responsibility of students from the first cycle to the second cycle because improvements were made to the techniques in giving varying sanctions in various ways, continuous coaching and motivation to class III.